STRATEGI IMAGE EKSKLUSIF ISLAMIC BOARDING SCHOOL DALAM PENDIDIKAN KARAKTER AGAMA - Annisa Yutha; Hanny Hafiar; Centurion C. Priyatna (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2019)
Diniyyah Puteri Boarding School its a first female boarding school in Southeast Asia established in 1923. The present study was conducted to identify the public understanding which related to establishment od exclusive image with Diniyyah Puteri in implementing the religious character. In addition, it aims to recognize the exclusive image strategy of Diniyyah Puteri Boarding School and to understand the differentiation of implementing the religious character in Diniyyah Puteri Boarding School, Padang Panjang.The research method used was qualitative method with case study. The data collected by multiple technique, namely interview, observation, and literature review. Symbolic interaction theory and exclusive image concept become the theory basis to compose the research result. The result of research founded a particular processing of establishment of exclusive image on Diniyyah Puteri, Padang Panjang. In its process of image establishment, strategy of Diniyyah Puteri Padang Panjang is to use the difference approach between internal and external publics. In the end, its exclusive image applied and implemented in religious character education with the expected output as the student who has the main character, namely devout and good moral, strong and tough as Mujahid God, intelligent and skilled as God’s steward.